Fuel Cell Systems Explained / Second Edition - Dicks Andrew; Larminie James (Wiley, 2003)
Assuming no prior knowledge of fuel cell chemistry, this reference comprehensively brings together all of the key topics encompassed by this diverse field. Preface, Acknowledgements, Abbreviations, Symbols, Introduction, Efficiency and Open Circuit Voltage, Operational Fuel Cell Voltages, Proton Exchange Membrane Fuel Cells, Alkaline Electrolyte Fuel Cells, Direct Methanol Fuel Cells, Medium and High Temperature Fuel Cells, Fueling Fuel Cells, Compressors and Turbines and Ejectors and Fans and Blowers and Pumps, Delivering Fuel Cell Power, Fuel Cell Systems Analyzed, Appendices, Change in Molar Gibbs Free Energy Calculations, Useful Fuel Cell Equations, Index.